Linking sustainability management and success in construction projects: Moderating influence of high performance work systems - Umer Zaman; Saba Abbasi; Shahid Nawaz; Muhammad Shahid Siddique (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
The environmental footprint of the global construction industry has emerged as a major concern in an era of massive urbanization across the world. Drawing on the complex and under-explored role of project sustainability management (PSM) and high performance work systems (HPWS), this study investigates the moderating role of HPWS between PSM and construction project success (CPS). Using survey of 368 project professionals working in the construction industry in Pakistan, the hypothesized relationships were tested with the partial least squares based structural equation modeling (PLS-SEM) technique. The study findings establish empirical support for the significant positive influence of PSM and HPWS on CPS. Moreover, the findings confirmed that HPWS positively moderates the effect of PSM on CPS. This research provides the initial evidence to confirm that PSM and HPWS are significant predictors of CPS, especially theeffects of PSM on CPS can be significantly enhanced by advancing HPWS in construction projects.
Keywords: 330; project sustainability management; HPWS; construction project success; China-Pakistan economic corridor (CPEC)